2015
DOI: 10.1016/j.appet.2015.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Association of usual self-reported dietary intake with ecological momentary measures of affective and physical feeling states in children

Abstract: Background Little is known about the relationship between dietary intake and affective and physical feeling states in children. Purpose The current study used Ecological Momentary Assessment (EMA) to examine how usual dietary intake is cross-sectionally associated with both average affective and physical feeling state ratings and rating variability in children. Methods Children (N = 110, mean age = 11.0 ± 1.2 years, 52.5% male, 30.1% Hispanic/Latino) completed EMA measures of affective and physical feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…There were no between-or withinsubjects actor effects for children. Other studies have found that the link between PA and fruit/vegetable intake does not extend to children (e.g., O'Reilly et al, 2015). The link between PA and fruit/vegetable intake may not develop until adolescence or adulthood.…”
Section: Estmentioning
confidence: 87%
See 2 more Smart Citations
“…There were no between-or withinsubjects actor effects for children. Other studies have found that the link between PA and fruit/vegetable intake does not extend to children (e.g., O'Reilly et al, 2015). The link between PA and fruit/vegetable intake may not develop until adolescence or adulthood.…”
Section: Estmentioning
confidence: 87%
“…The MATCH Study is unique in that it utilizes multiple waves of EMA data spaced approximately 6 months apart to capture real-time information on stress, affect, and diet intake behaviors within school-age children (age 8 -12 years) and their mothers. Additional information about the MATCH Study design can be found elsewhere (Dunton et al, 2015). An ethnically and racially diverse group of mothers and children was recruited from southern California schools through study flyers distributed to classrooms, and information booths at school and community organized events.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…27,30 Another reported higher subject-level variability of NA across the EMA period correlated with more unhealthy dietary intake. 31 Therefore, NA patterns across the day may predict unhealthy eating above and beyond NA levels at any given time point. Using latent growth mixture modeling of days with EMA data, studies have identified daily mood trajectories of NA and anxiety associated with disordered eating behaviors such as binge eating, purging, and skipping meals.…”
Section: Introductionmentioning
confidence: 99%
“…Plausible mechanisms have been proposed whereby the stimulation of SCFA production and alteration of the colonic microbiome can influence systemic oxidative stress and inflammation and thereby influence both physical and mental functioning [ 15 , 16 , 17 ]. In this context, it is of interest that higher self-reported fiber intake was associated with higher positive affect in healthy children [ 18 ] and, in a randomized, cross-over study, consumption of a high fiber breakfast cereal for 2 weeks was associated with less fatigue compared to control in healthy adults [ 19 ]. We found that participants with type 2 diabetes treated by diet alone who consumed a low glycemic index diet containing 37 g/day fiber for 1 year experienced less severe headaches, less severe pains in joints or limbs and less severe gloomy thoughts than those on the lower fiber (21–23 g/day) diets [ 20 ].…”
Section: Introductionmentioning
confidence: 99%